(3QSGdI jQO HgG Ydi CMO GdeYJQVjf Ydi CHh GdaQLs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bGd CYQV Ydi ajeG hLOg GdTjN GHh GdaQL ef GdENdGd hGdGNJdGW ai ebGdI di cJHJgG dbO CedjJ gPg GdQSGdI ai MGd HbjI CeQGV s
(3BNQgG (B:s
(3hdYd Gddg SJQ GdeTGagI ajchf GdJaGhV ajg Ydi cJeGf Ef SCd Gddg hMOg JeJ GdQSGdI hGdMeO ddg cKjQkG s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs